Factors Associated with Adverse Effects in Elderly Women Receiving Chemotherapy for Breast Cancer - Raza, Ahmed; Amin, Zulfiqar Ali; Nadeem, Muhammad; Umair, Muhammad; Khan, Amjad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyze the factors associated with adverse effects in elderly women receiving chemotherapy for breast cancer. Study Design: Comparative Cross-sectional Study. Place and Duration of Study: Oncology Department, Combined Military Hospital (CMH), Rawalpindi Pakistan, from Dec2020 to Nov 2021. Methodology: This study was conducted on 145 female patients (>65 years) with breast cancer who were taking chemotherapy of any type and had undergone one cycle. All the study participants underwent detailed clinical evaluation by a consultant oncologist to assess the presence of various adverse effects of chemotherapy. In addition, the association of Anthracycline use,>3 months of treatment, low haemoglobin at baseline and abnormal liver functions at baseline were studied with adverse effects in the study participants. Results: The final analysis included one hundred forty-five elderly female patients with breast cancer receiving chemotherapy.The mean age of the patients was 69.731±8.794 years. 89(61.4%) patients had no adverse effects, while 56(38.6%) had one or more adverse effects during chemotherapy. Anaemia 26(17.9%) was the commonest adverse effect, followed by fatigue 18(12.4%) and abnormal liver function tests 18(12.4%). It was revealed that the use of Anthracycline-based chemotherapy and long duration of chemotherapy were statistically significantly associated with adverse effects (p-value<0.05) in our study participants. Conclusion: Considerable number of elderly patients with breast cancer undergoing chemotherapy showed the presence of adverse effects. In addition, patients using Anthracycline-based chemotherapy and taking chemotherapy for more than three months were more at risk of developing adverse effects.